Implementation of the Talaqqi Method in Increasing the Qur’an Learning Achievement of Class 6 Students - Najrul Jimatul Rizki; Rubi Babullah; Kun Nurachadijat (P3M IAI Nusantara Batang Hari, 2023)
The talaqqi method is a learning approach that focuses on direct interaction between teachers and students. The aim of this method is to improve learning achievement through a personal approach that involves deep understanding, reflection, and individual coaching. In the context of education, the talaqqi method has proven effective in optimizing learning outcomes. This study aims to investigate the effect of the talaqqi method on student achievement. The talaqqi method provides opportunities for students to engage in in-depth interactions with the teacher, obtain direct feedback, and reflect on the subject matter. This helps improve students' understanding of concepts, cognitive skills, and learning motivation. In addition, the talaqqi method also has a positive impact on forming close relationships between teachers and students. Teachers can recognize the individual needs of students and provide appropriate coaching. Students feel more comfortable and actively involved in the learning process, thus creating a sense of responsibility for their own achievements. The implementation of the talaqqi method in learning the Koran begins with memuraja'ah with the letters that have been memorized. Then the teacher mentally recites or reads the verses that the children will read or memorize. After the teacher reads it, the students reread the verses that have been read over and over again so that the child can quickly read and memorize when the verses are memorized.